Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - 2.3 - Analyzing Graphs of Functions - 2.3 Exercises - Page 195: 63



Work Step by Step

$f(x)=x^3-3x^2-x$ Determine the average rate of change from $x_1=-1$ to $x_2=2$: $\dfrac{f(x_2)-f(x_1)}{x_2-x_1}=\dfrac{f(2)-f(-1)}{2-(-1)}$ $=\dfrac{[2^3-3(2^2)-2]-[(-1)^3-3(-1)^2-(-1)]}{3}$ $=\dfrac{-6-(-3)}{3}$ $=-1$ The average rate of change is -1.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.